(−)‐Epicatechin‐induced relaxation of isolated human saphenous vein: Roles of K+ and Ca2+ channels. (29th November 2017) - Marinko, Marija; Jankovic, Goran; Nenezic, Dragoslav; Milojevic, Predrag; Stojanovic, Ivan; Kanjuh, Vladimir; Novakovic, Aleksandra
Abstract : In this study, we aimed to investigate relaxant effect of flavanol (−)‐epicatechin on the isolated human saphenous vein (HSV), as a part of its cardioprotective action, and to define the mechanisms underlying this vasorelaxation. (−)‐Epicatechin induced a concentration‐dependent relaxation of HSV pre‐contracted by phenylephrine. Among K + channel blockers, 4‐aminopyridine, margatoxin, and iberiotoxin significantly inhibited relaxation of HSV, while glibenclamide considerably reduced effects of the high concentrations of (−)‐epicatechin. Additionally, (−)‐epicatechin relaxed contraction induced by 80 mM K +, whereas in the presence of nifedipine produced partial relaxation of HSV rings pre‐contracted by phenylephrine. In Ca 2+ ‐free solution, (−)‐epicatechin relaxed contraction induced by phenylephrine, but had no effect on contraction induced by caffeine. A sarcoplasmic reticulum Ca 2+ ‐ATPase inhibitor, thapsigargin, significantly reduced relaxation of HSV produced by (−)‐epicatechin. These results demonstrate that (−)‐epicatechin produces endothelium‐independent relaxation of isolated HSV rings. Vasorelaxation to (−)‐epicatechin probably involves activation of 4‐aminopyridine‐ and margatoxin‐sensitive KV channels, BKCa channels, and at least partly, KATP channels. In addition, not only the inhibition of extracellular Ca 2+ influx, but regulation of the intracellular Ca 2+ release, via inositol‐trisphosphate receptors and reuptake into sarcoplasmic reticulum, via stimulation of Ca 2+ ‐ATPase, as well, most likely participate in (−)‐epicatechin‐induced relaxation of HSV.